PIN diode equivalent circuit modelling - Zhu, Yuxiang (Nanyang Technological University, 2023)
In this dissertation, the equivalent circuit and their elements parameters of SMP-1340-040 and MA4AGP907 PIN diodes are modelled and extracted for both forward and reverse bias. The MA4AGP907's forward bias equivalent circuit has S11 that differs from the measured data by no more than 2dB in magnitude at frequencies from 2GHz to 45GHz and by no more than 5dB in magnitude at frequencies from 45GHz to 50GHz, also the difference is not higher than 8 degrees in phase from the measured data at frequencies from 2GHz to 50GHz. The MA4AGP907's reverse bias equivalent circuit of S21 deviates from the measured data by no more than 0.75dB and 5.2 degrees in magnitude and phase at frequencies from 2GHz to 50GHz respectively. The SMP-1340-040's forward bias equivalent circuit of S11 deviates from the measured data by no more than 5dB and 10 degrees in magnitude and phase at frequencies from 1GHz to 4GHz respectively. The SMP-1340-040's reverse bias equivalent circuit of S21 deviates from the measured data by no more than 1.2dB and 9 degrees in magnitude and phase at frequencies from 1GHz to 4GHz respectively. In addition, a standardised method for extracting the equivalent circuit of a PIN diode is summarised. This standardised procedure with a clear discriminatory approach makes it possible to automate the extraction of PIN diode equivalent circuit models by computer. In practice, once the correct circuit model has been obtained, various parameters in the circuit can be optimised by the algorithms that come with the EDA software to improve the fit.